When the Truth Doesn't Seem to Matter: The Affordances of Disciplinary Argument in the Era of Post-truth. (April 2023) - Ferretti, Ralph P.
A disquieting aspect of some contemporary public discourse is its seeming indifference to or abandonment of any pretense to truth. Among other things, unsubstantiated and misleading claims have been made about the efficacy of vaccines and other purported treatments for SARS-COVID, the 2020 U.S. presidential election, and the January 6, 2021, insurrection on the U.S. Capitol. In addition, a spate of legislation restricting classroom discussion and instruction related to race, bias, privilege, and discrimination has been or is pending passage in U.S. state legislatures. These restrictions are antithetical to core functions of education, which are to inculcate the values, virtues, and advanced literacy skills that support democratic deliberation about controversial issues. This article discusses the increasing political polarization and partisan attacks on the processes of education and the threats to liberal democracy posed by this disregard for the truth. In addition, it reviews the cultural and psychological factors that increase our susceptibility to misinformation and presents a perspective about the pursuit of truth that highlights the educational affordances of disciplinary inquiry, democratic deliberation, and reasonable argumentation. The contemporary challenges are manifestations of long-standing political and cultural divisions, and their mitigation will depend on developing communities of informed citizens that are committed to the values and virtues that are foundational to liberal democracy.